Label-free single-molecule identification of telomere G-quadruplexes with a solid-state nanopore sensor. Issue 45 (21st July 2020) - Wang, Sen; Liang, Liyuan; Tang, Jing; Cai, Yao; Zhao, Chuanqi; Fang, Shaoxi; Wang, Huabin; Weng, Ting; Wang, Liang; Wang, Deqiang
Abstract : Nanopore detection of single-molecule G-quadruplexes. Abstract : Telomere sequences can spontaneously form G-quadruplexes (G4) in the presence of some cations. In view of their relevance to genetic processes and potential as therapeutic-targets, hitherto, a wealth of conventional techniques have been reported for interrogation of G4 conformation diversity and corresponding folding kinetics, most of which are limited in precision and sensitivity. This work introduces a label-free solid-state nanopore (SSN) approach for the determination of inter-, intra- and tandem molecular G4 with distinct base permutation in various cation buffers with a tailored aperture and meanwhile captures the single-molecule G4 folding process. SSN translocation properties elucidated that both inter- and intramolecular G4 generated higher current blockage with longer duration than flexible homopolymer nucleotide, and intramolecular G4 are structurally more stable with higher event frequency and longer blockage time than intermolecular ones; base arrangement played weak role in translocation behaviors; the same sequences with one, two and three G4 skeletons displayed an increase in current blockage and a gradual extension in dwell time with the increase of molecule size recorded in the same nanopore. We observed the conformation change of single-molecule G4 which indicated the existence of folding/unfolding equilibration in nanopore, and real-time test suggested a gradual formation of G4 with time. Our results could provide a continued and improved understanding of the underlying relevance of structural stability and G4 folding process by utilizing SSN platform which exhibits strategic potential advances over the other methods with high spatial and temporal resolution.